Forschungsforum "Begriffsklärungen in Wissenschaft und Bildung: Entscheidung" - Bleicher, Alena; Fink, Sascha-Michael Benjamin; Funke, Joachim; Göbel, Elisabeth; Krischer, André; Martin, Albert; Priddat, Birger P.; Reese-Schäfer, Walter; Rieber, Viktoria; Köhler-Saretzki, Thomas (Inter- und transdisziplinäre Bildung, 2021)
Kein Abstract
Gesehen am 02.05.2022